Active production of the scale and food sovereignty: the case of the street market in the municipality of Pacaembu, São Paulo State, Brazil (2017-2019) - Valerio, Valmir Jose de Oliveira [UNESP] (Univ Federal Goias, Inst Estudos Socio-ambientais, 2023)
The current hegemonic system of food production and supply submits producers and consumers to the sieve of dependence on the chains of middlemen, making the separation between the two constituting the resource with which commercial and industrial capital controls production, distribution and consumption. In this context, as a spatial expression of contradictory processes of competition and cooperation, the concept of active production of the scale presents possibilities for overcoming the relationships of dependence and subordination derived from the hegemonic food system, offering paths for the emancipation of food relations. Indeed, this article aims to analyze the elements that support the construction of an alternative food system, based on the principles of active production of the scale and food sovereignty. For this, we present examples resulting from the literature review and field work, with special attention to the case of the street market in the municipality of Pacaembu, Sao Paulo state, Brazil. In different ways, these cases show that, despite the multiple adversities, the rapprochement between producers and consumers brings with it the substrate that paves the way for the transition from dependence to sovereignty and, consequently, for the emancipation of food and eating habits.
Keywords: Food system; Active production of the scale; Food sovereignty; Emancipation